Behaviorally-Mediated Entrainment of Whole-Body Metabolic Processes: Conservation and Evolutionary Development of Mitochondrial Respiratory Complexes - Stefano, George B; Esch, Tobias; Kream, Richard M (Medical Science Monitor, 2019)
The relaxation response derives its health benefits by reestablishing "normal" equilibria between the sympathetic and parasympathetic branches of the autonomic nervous system. Recent work suggests that this behavioral training provides positive effects on mitochondrial bioenergetics, insulin secretion, and reductions in pro-inflammatory and stress-related pathways. We have previously contended, however, that correlative associations of relaxation training with positive changes in gene expression in selected biological systems are strongly suggestive of adaptive physiological changes, but do not elucidate an underlying, clinically compelling, unified mechanism of action consistent with its purported positive health effects. We surmise that any plausible model of behaviorally-mediated regulatory effects on whole-body metabolic processes must be intrinsically broad-based and multifaceted via integration of differential contributions of functionally interactive peripheral and CNS organ systems. Accordingly, the initiation of multiple cellular protective/anti-bio-senescence processes may have emerged during evolutionary development to ensure the survival of hybrid prokaryotic/eukaryotic progenitor cells, given the evolvement of oxidative metabolism and its associated negative byproducts. As an essential corollary, preservation and adaptation of multifaceted regulatory molecules, notably nitric oxide, paralleled the development of eukaryotic cell types via multifaceted stereo-selective recognition and conformational matching by complex biochemical and molecular enzyme systems. Hence, the relaxation response may be a manifestation of a metabolic corrective process/response, that may now include cognition ("awareness").
Keywords: relaxace; Humans; Mitochondria; zvířata; oxid dusnatý; Nitric Oxide; spotřeba kyslíku; Adenosine Triphosphate; buněčné dýchání; mitochondrie; adenosintrifosfát; energetický metabolismus; Energy Metabolism; Oxygen Consumption; Cell Respiration; Animals; lidé; teoretické modely; Relaxation; Models, Theoretical